Structure-activity relationships of N-benzylsalicylamides for inhibition of photosynthetic electron transport - Kralova, Katarina; Perina, Milan; Waisser, Karel; Jampilek, Josef (Medicinal chemistry, 2015)
Inhibition of photosynthetic electron transport (PET) in spinach chloroplasts by sixty-one ring-substituted N-benzylsalicylamides was investigated. The inhibitory potency of the compounds expressed by IC50 value varied from 2.0 to 425.3 μmol/L. Several evaluated compounds can be considered as effective PET inhibitors; these include N-(3,4- dichlorobenzyl)-2-hydroxy-5-nitrobenzamide (IC50 = 2.0 μmol/L), 3,5-dibromo-N-(3,4-dichlorobenzyl)-2-hydroxybenzamide (IC50 = 2.3 μmol/L) and 3,5-dibromo-N-(4-chlorobenzyl)-2-hydroxybenzamide (IC50 = 2.6 μmol/L) with activity comparable with that of the standard Diuron (IC50 = 1.9 μmol/L). The PET inhibiting activity increased approximately linearly with increasing lipophilicity of the compounds as well as with the increasing sum of Hammett σ constants of the substituents on the acyl fragment (R(1) = H, 5-OCH3, 5-CH3, 5-Cl, 5-Br, 5-NO2, 4-OCH3, 4-Cl, 3,5-Cl and 3,5-Br) and the benzylamide fragment (R(2) = H, 4-OCH3, 4-CH3, 4-F, 4-Cl and 3,4-Cl). Based on the evaluated structure-PET inhibiting activity relationships (QSAR) it was confirmed that the inhibitory activity of the compounds depends on lipophilicity (log P or distributive parameters π; (1) and π(2)of individual substituents) and electronic properties of the substituents on the acyl (σ(1)) and the benzylamide fragments (σ(2)), the contribution of σ(1) being more significant than that of σ(2).
Keywords: Salicylamides; kvantitativní vztahy mezi strukturou a aktivitou; chemické modely; Quantitative Structure-Activity Relationship; fotosyntéza; Spinacia oleracea; chloroplasty; Photosynthesis; racionální návrh léčiv; transport elektronů; salicylamidy; Chloroplasts; Molecular Structure; Drug Design; molekulární struktura; Electron Transport; Models, Chemical